An analysis of the coverage of Helen Zille and Patricia De Lille prior to, during and after South Africa's national elections by South African English newspapers - Ohlhoff, Heinrich (Carl Heinrich Friedrich) (University of Pretoria, 2021)
Dissertation ( MA)- University of Pretoria, 2021.